Coverage under old age security programs and protection for the uninsured : what are the issues? - James, Estelle (Policy research working paper, 1999)
The shift toward social security systems with a tighter link between benefits and contributions will make such systems more fiscally sustainable. But to protect the uninsured and underinsured, such programs should be complemented by better social assistance programs for low-income groups